Classificar é preciso? Uma análise sobre as representações do rural e urbano no distrito de Cruzeiro dos Peixotos em Uberlândia - MG - Nazareth, Carolina Cadima Fernandes (2015)
The present dissertation analyze the representation between the rural and urban in one district in the city of Uberlândia (MG) calling as Cruzeiro dos Peixotos, For this, the analyze was realize in three moments, first, by analyze of local history and the bibliographic of the theme in the Social Science. The last two chapter of the study covers the urban representation, through of the rural work, by Folia de Reis. For this, analyses beteween the “inside” and “the outside” (or “others”), was constantly addressed. Finally, this work search, through the district, understand and explain what specific classification limit places which are located in the “inset” rural/urban, and the analyze of the native representation are fundamental for understand the possibility of this transit between this two possible universe of the district. Terms like hybridity and continuun will be addressed.